2013
DOI: 10.1002/grl.50303
|View full text |Cite
|
Sign up to set email alerts
|

Lower tropospheric ozone at northern midlatitudes: Changing seasonal cycle

Abstract: [1] At northern midlatitudes the abundance of tropospheric O 3 has increased by a factor of approximately 2 since the 1950s. The cause of this increase is generally attributed to increasing anthropogenic precursor emissions, but present chemical and transport models cannot quantitatively reproduce its magnitude. Here we show another manifestation of changes in O 3 abundance-a shift of the seasonal cycle at northern midlatitudes so that the observed peak concentrations now appear earlier in the year than in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
113
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 38 publications
11
113
1
Order By: Relevance
“…Meanwhile, in East Asia, surface ozone is generally increasing where ozone precursor emissions are growing. Parrish et al (2013) demonstrate that another manifestation of changes in tropospheric O 3 is a shift of the seasonal cycle at northern mid-latitudes, so that the observed peak concentrations now appear earlier in the year than they did in previous decades (see Fig. 7).…”
Section: Changing Ozone -A Brief Historymentioning
confidence: 60%
See 2 more Smart Citations
“…Meanwhile, in East Asia, surface ozone is generally increasing where ozone precursor emissions are growing. Parrish et al (2013) demonstrate that another manifestation of changes in tropospheric O 3 is a shift of the seasonal cycle at northern mid-latitudes, so that the observed peak concentrations now appear earlier in the year than they did in previous decades (see Fig. 7).…”
Section: Changing Ozone -A Brief Historymentioning
confidence: 60%
“…The rate of this shift has been about 3 to 6 days per decade since the 1970s. Parrish et al (2013) put forward an untested hypothesis that this shift may be due to changes in atmospheric transport patterns combined with spatial and temporal changes in emissions. This study relied on three long-term (> 20 years) rural data sets in western Europe and one in the western USA.…”
Section: Changing Ozone -A Brief Historymentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonal peak of ozone in the northern midlatitudes typically occurs in summer over populated continental areas, due to local and regional photochemical production and in late spring for remote continental areas, due to both enhanced stratospheric input and photochemical production in that season (Monks, 2000;Parrish et al, 2013). Recently, a shift in the seasonal peak towards an earlier time in year has been observed at several high elevation sites Parrish et al, 2013).…”
Section: Long-term Trends Of Ozonementioning
confidence: 99%
“…Carslaw (2005), Bloomer et al (2010), and Parrish et al (2013) found multidecadal changes in the amplitude and phase of the seasonal cycle at NH mid-latitudes. It was suggested that these changes can be attributed to changes in atmospheric transport patterns combined with spatial and temporal changes in emissions.…”
Section: Seasonal Variationmentioning
confidence: 95%